The Little data book 2002 World Bank.. (World Bank, 2002)
"This is the pocket edition of the World Development Indicators for 2002, intended as a quick reference for users. It presents the latest available data for World Bank member countries, and other economies with populations of more than 30,000. The 14 summary pages cover regional and income group aggregates. The data in this book are for 1990, 1999, and 2000 or the most recent year unless otherwise noted in the glossary."